Impact of environmental pollution on human health: Investigating the role of Polycyclic Aromatic Hydrocarbons in pediatric osteosarcoma - Mingxian Xu; Yu Xu; Yaping Huang; Jixiang Shi; Lifeng Yin; Jian Tu; Junqiang Yin; Changye Zou (Ecotoxicology and Environmental Safety)
Background: Polycyclic aromatic hydrocarbons (PAHs), widely emitted through industrial processes and vehicular exhaust, are recognized environmental carcinogens. Although PAH exposure has been linked to various malignancies, the specific molecular mechanisms underlying its involvement in pediatric osteosarcoma remain poorly defined. Methods: This study analyzed residential and environmental data from 345 pediatric osteosarcoma patients diagnosed between 2000 and 2019 to explore potential correlations with environmental PAH exposure. A total of 1617 candidate PAH-associated molecular targets were retrieved from bioinformatics databases (PubChem, STITCH, GeneCards, DisGeNET), and core targets were identified using STRING and Cytoscape network analyses. Molecular docking was conducted to assess interactions between selected targets and two major PAH compounds, naphthalene (NAP) and benzo[a]pyrene (BaP). In parallel, serum PAHs-DNA adduct concentrations were quantified in 41 patients, and their associations with residential location and clinical outcomes were examined. Results: The analysis refined the initial candidate list to 14 core molecular targets. Among these, ACTB, EGFR, and JUN were identified as key prognostic genes through survival analysis and machine learning models. These genes were enriched in oncogenic pathways, including the PI3K-Akt signaling pathway. Molecular docking confirmed strong binding affinities between NAP/BaP and the three core targets. Clinically, serum PAHs-DNA adduct levels were significantly higher in patients from highly urbanized areas compared to less developed regions (443.9 pg/mL vs. 146.4 pg/mL, p < 0.0001) and were associated with reduced overall survival (p = 0.0091). Conclusion: This study presents the first systems-level investigation elucidating potential molecular mechanisms linking PAH exposure to pediatric osteosarcoma. The identification of ACTB, EGFR, and JUN as environmentally responsive oncogenic mediators offers a mechanistic framework for future validation. These findings support the utility of computational toxicology in environmental risk assessment and highlight potential molecular targets for the prevention and treatment of pediatric osteosarcoma.